2006
DOI: 10.1016/j.jacc.2005.11.074
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the Metabolic Syndrome and its Relation to Cardiovascular Disease in an Elderly Chinese Population

Abstract: The MetS is highly prevalent in elderly people in Beijing, particularly among women. Individuals with MetS defined by either criteria are at significantly elevated ORs for CHD, stroke, and PAD. The IDF criteria seem to be better suited than the NCEP criteria for screening and estimating risk of MetS in Chinese people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
158
14
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 199 publications
(205 citation statements)
references
References 15 publications
22
158
14
6
Order By: Relevance
“…17 Outside the US, the prevalence of MetS ranges from 15% to 38%. 18 We found a higher prevalence of MetS than previous US reports and also evaluated the impact of MetS on mortality in patients with HF from an indigent HFDM population. Prospective cohorts 6,11,12,19 -22 and a meta-analysis of those studies 2 found a clear association between mortality and MetS.…”
Section: Discussionmentioning
confidence: 55%
“…17 Outside the US, the prevalence of MetS ranges from 15% to 38%. 18 We found a higher prevalence of MetS than previous US reports and also evaluated the impact of MetS on mortality in patients with HF from an indigent HFDM population. Prospective cohorts 6,11,12,19 -22 and a meta-analysis of those studies 2 found a clear association between mortality and MetS.…”
Section: Discussionmentioning
confidence: 55%
“…People of south Asian origin wherever they are settled have an increased vulnerability to coronary artery disease (CAD) and type 2 diabetes, compared to indigenous populations [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The cause of increased susceptibility of south Asians to CAD and diabetes may be due to MS [20,22].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of MS in our study was 19.3% (n=387) including 19.8% among men and 18.7% among women. MS has been observed in many ethnic groups and it is estimated that it is prevalent in approximately one fourth of the adult population of the world [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. In a multicenter case control study from India, involving 5088 subjects with known type 2 diabetes, the overall prevalence of MS was 77.2%, and the rates were significantly higher among women compared to men, respectively (87.7 vs. 69.3%, P<0.0001) [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations